Lylye of medicynes: an edition of the fifteenth-century translation of Bernard of Gordon’s Lilium medicinae - Connelly, Erin (2016)
This is an edition of the Middle English Lylye of Medicynes, a fifteenth-century translation of Bernard of Gordon’s Latin Lilium Medicinae (completed in 1305). The Lylye is contained in Oxford Bodleian Library MS. Ashmole 1505 as a sole text. Although there are multiple witnesses in Latin, there are no other known Middle English witnesses of this text. The Lylye is arranged in a ‘head to toe’ format (beginning with diseases of the head and proceeding downward) with accompanying guidelines for diagnosis and prognosis. Although the text does contain some medical theory and aetiology (based on thought from Arabic medicine, specifically Ibn Sīnā, and Antiquity, predominantly Galen and Hippocrates), it is mainly comprised of a large volume of medicinal recipes and treatments.